Utilization AI for Socially Responsive Education as a Path to Inclusive Development - Loso Judijanto; M. Anwar Aini; Asfahani Asfahani; Zohaib Hassan Sain; Arnes Yuli Vandika (Edujavare Publishing, 2022)
The integration of Artificial Intelligence (AI) into educational practices has garnered increasing attention as a potential pathway to fostering inclusive development. This study investigates the utilization of AI for socially responsive education, aiming to explore its opportunities, challenges, and implications for promoting inclusivity in educational settings. Through qualitative research methods including interviews, focus groups, and document analysis, key findings emerge highlighting the potential of AI to personalize learning experiences and expand access to education, particularly in underserved communities. However, the study also identifies concerns regarding algorithmic bias, the digital divide, and ethical considerations, emphasizing the need for collaborative efforts among stakeholders to ensure the responsible and equitable deployment of AI technologies in education. The analysis of research findings contributes to a nuanced understanding of the complex dynamics surrounding AI in education and underscores the importance of advancing inclusive development agendas through the strategic integration of AI into educational practices.